Synthesis, characterization and application of a novel polyazo dye as a universal acid–base indicator. Issue 43 (3rd October 2022) - Naime, Jannatul; Mamun, Muhammad Shamim Al; Aly Saad Aly, Mohamed; Maniruzzaman, Md; Badal, Md Mizanur Rahman; Karim, Kaykobad Md Rezaul
Abstract : A novel polyazo dye (SDMAPD3BS) was synthesized and its application as a universal acid–base indicator was investigated. This molecule can be used as a universal indicator for all types of acid–base reactions. Abstract : A novel organic polyazo dye is synthesized by the diazotization of aromatic aniline, followed by coupling it with sulfanilic acid and N, N -dimethylaniline. Characterization was done by 1 H-NMR, 13 C-NMR, and FTIR spectroscopy. Differential scanning calorimetry (DSC) reveals that phase transition for this molecule is exothermic. The optical band gap is estimated from the absorption cutoff point using UV-Visible spectroscopy. Thermal gravimetric analysis (TGA) addresses the thermal stability of the molecule and is found to be at ∼250 °C. The structure of the synthesized molecule is analogous to that of methyl orange and contains three azo groups. These three azo groups help accept more than two protons and provide two p K a values when diprotic acid or a mixture of acids is used in different titrations. Specifically, when a polybasic acid is in strong base titration, the p K a values were found to be 3.5 and 9.1. Moreover, for strong base and (strong + weak) acid mixture titration, the p K a values are found to be 9.2 and 3.3. Furthermore, the p K a values are found to be 8.6 and 2.8 for (strong and weak) base mixture and (strong and weak) acid mixture titration, respectively. Owing to its increased proton accepting capacity, it can be found in the two pH ranges of 2.1–3.8 for orange color and 8.2–9.8 for yellow color, thus indicating a unique property as a universal indicator for acid–base titration. The dissociation constant of this dye is found to be 3.4 × 10 −6, determined in a mixed aqueous solution of 10 wt% ethanol, and a linear relationship between p K a and pH is observed in this solvent system.